The Use of MSK Ultrasound with Quadriceps Muscle Injury - Robert C Manske; Michael Voight; Chris Wolfe; Phil Page (International Journal of Sports Physical Therapy)
Quadriceps muscle injury is a common occurrence, especially among athletes. While a careful history and a thorough physical examination are important steps in the assessment of quadriceps muscle pathology, it is still difficult to differentiate the type and severity of the pathology. Because of this difficulty, musculoskeletal ultrasound (MSK-US) is an invaluable tool in the diagnosis of quadriceps muscle or tendon injury. Utilizing this noninvasive imaging technique, medical professionals can easily diagnose and monitor muscle and tendon disorders to quickly determine the correct treatment plan for each individual case. The ability to view these structures in real-time allows identification of any present pathologies. MSK-US has become a useful component in diagnosing quadriceps muscle and tendon injuries due to its ability to clearly display the affected structures without exposing the patient to radiation or utilizing ionized contrast media. MSK-US provides valuable insight into fluid dynamics around joints and can even detect myotendinous tears that might otherwise be overlooked with the clinical examination or symptoms usually reported by patients. MSK-US can provide precise visualization of edema and can easily distinguish between benign and potentially pathological findings which make it an integral part of any holistic evaluation of quadriceps muscle and tendon injury. Additionally, it can be used to track the progress of physical therapy treatments and monitor tissue healing. This information is invaluable in ensuring an optimal outcome for any quadriceps muscle and tendon injury. Therefore, when used in combination with clinical tests, MSK-US can drastically increase the accuracy of the clinical examination. By utilizing this technology, healthcare practitioners have reliable access to more comprehensive diagnostics for musculoskeletal injuries and diseases than ever before. Clinicians are then able to tailor rehabilitation plans more effectively and ensure their patients receive proper treatment. As a result, recovery times may be shortened, and patients are able to return to their normal activities more quickly.